Evaluasi Pengadaan dan Penyaluran Pupuk Bersubsidi di PT. Pusri Studi Kasus Kabupaten Banyuasin - Muhammad Febrianza; Marleni Marleni; Nopriawan Mahriadi (Universitas Muara Bungo, 2025)
This study aims to examine the provision of subsidized fertilizer by the government in Banyuasin district to increase productivity and farmer income and a sustainable environment. This study is to evaluate the distribution of subsidized fertilizer. The research method uses a qualitative approach, the object of the Banyuasin district government, data collection, observation, interviews, documentation, conducted to the Banyuasin district government as a regulator, PT PUSRI, the provider of subsidized fertilizer policies as well as distributors of subsidized fertilizers and the community and farmers receiving subsidized fertilizers. The presentation of data is descriptive qualitative using the analysis of the CIPP (Context, Input, Process, Product) evaluation model theory by Stufflebeam. The results of the study indicate that the implementation of subsidized fertilizer distribution in Banyuasin Regency still requires improvement. The Context evaluation of the obstacles is not in accordance with the 6T principle of the right type, the right amount, the right price, the right place, the right time, and the right quality. The input for evaluating the source of funds in the procurement and distribution process is taken from the APBN funds and the PNBP Migas advances from the oil and gas profit sharing between the government. The distribution process of PT PUSRI that every farmer who wants to get subsidized fertilizer must have a Farmer Card. The impact of the product can be felt by farmers, the positive impact for farmers who have received the Farmer Card they feel no longer have difficulty in purchasing fertilizer, but the negative impact where the inequality of fertilizer recipients is caused by inaccurate data collection makes farmers buy fertilizer at commercial prices. In the process of conveying information by Banyuasin Regency in implementing the program, socialization is carried out evenly so that the public is aware of the policy regarding the procurement of subsidized fertilizer. For PT PUSRI, it is better to cooperate with the Ministry of Agriculture in updating data. Distribution of subsidized fertilizer can involve village or regional governments and law enforcement officers.